Peningkatan pencapaian HOTS siswa pada materi gerak parabola dan gerak melingkar menggunakan LKS berorientasi model inkuiri terbimbing di SMAN 2 Pariaman - Dara Putri Pratama; Yenni Darvina; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2020)
Physics is a subject that can change people become productive, creative, and innovative. Physics lesson require students to understand and to solve existing environmental problems in real life. The ability to think critically, creatively, collaborativelly and communicate can be developed to prepare students to face challenges in the 21st century. However, the real conditions in schools show that physics is not running optimally. In order to help the learning process, learning resources are needed. One of the learning resources needed to overcome this problem is teaching material in the form of Student Worksheet. This research is intended to know the effectiveness of worksheet based on a guided inquiry to grow the higher order thinking on parabolic motion and circular motion. The design in this research is one group pretest-posttest design. The data analysis technique by using the N-gain test and effect size. The result of this research shows that Student Worksheet effective as learning innovation based on higher order thinking skill include analyzing (C4), evaluating (C5), and creating (C6) into a high category with N-gain 0,82. Student Worksheet effectiveness based on the results obtained using effect size of 0,83 to analyze, evaluate and create.